1997
DOI: 10.1002/elps.1150180523
|View full text |Cite
|
Sign up to set email alerts
|

Computer analysis of two‐dimensional electrophoresis gels: A new segmentation and modeling algorithm

Abstract: The complexity of the spot patterns of two-dimensional electrophoresis gels made it necessary to use image processing techniques to analyze the gels. An important issue in the analysis is the detection and quantification of the protein spots. In this paper we describe a new technique to segment and model the different spots. For the segmentation of a gel into its different spot regions we apply a watershed technique, which is robust and efficient. For the quantification of the spots, a new spot model is constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Both the main-body and the inner-dip 3D curves are expressed as the diffusion function C(x,y) proposed by Bettens et al [20], and therefore resemble the 3D Gaussian or plateau curve. Moreover, their orientation is opposite; the base of the main-body of the spot-model is down and its peak is up, while the base of the inner-dip of the spot-model is up and its peak is down (Fig.2).…”
Section: A Morphological Models For a Microarray Spot And Its Comparmentioning
confidence: 99%
“…Both the main-body and the inner-dip 3D curves are expressed as the diffusion function C(x,y) proposed by Bettens et al [20], and therefore resemble the 3D Gaussian or plateau curve. Moreover, their orientation is opposite; the base of the main-body of the spot-model is down and its peak is up, while the base of the inner-dip of the spot-model is up and its peak is down (Fig.2).…”
Section: A Morphological Models For a Microarray Spot And Its Comparmentioning
confidence: 99%
“…Such manual operations have serious effects on the estimation of the spot volume and the location of the spot centroid (center of gravity). Recently, other methods have been applied, such as watershed transformation 5) , which can segment spots in 2-DE gel [6][7][8] , but cannot segment spot regions if the spots are connected to one another by the saturated black spots.…”
Section: Introductionmentioning
confidence: 99%
“…This model is assumed to provide a good representation of most spots present in most gel images. However, it has been shown that Gaussian models produce an inadequate fit to some protein spots, most notably large volume, saturated spots [1]. Figure 2(b) shows an example of a high volume protein spot exhibiting a saturated, 'flat-top' shape.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2(b) shows an example of a high volume protein spot exhibiting a saturated, 'flat-top' shape. Bettens [1] addressed this shortcoming by proposing a model based on the physics of the spot formation process. Protein spots are formed by a diffusion process, which is only adequately represented by a Gaussian when the initial concentration distribution occupied by the sample has a small area.…”
Section: Introductionmentioning
confidence: 99%